PENGARUH LAMA ADSORBSI EKSTRAK SANSEVIERIA (LIDAH MERTUA) SEBAGAI ADSORBEN LOGAM Ag DARI LIMBAH INDUSTRI PERAK DI KOTAGEDE - Sukci Winanti, Aan Dwi Nurcahyo, Erista Yusron Mubarok (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The research is aimed at finding out the effect of the adsorption duration Sansevieriaextract as Ag adsorbent from the industrial waste of silver in Kotagede. Besides, the researchis also aimed at determining the effectiveness of Sansevieria extract in adsorbing Ag metalfrom the industrial waste of silver in Kotagede by using AAS (Atomic AbsorptionSpectrophotometry) test.The research method included preparing samples of Sansevieria, extracting Sansevieria,testing Sansevieria extract as adsorbent of Ag in the industrial waste of silver in Kotagedewith two variations of soaking time, 2 days and 3 days, and testing the liquid waste andSansevieria extract by using AAS after the soaking process.The research results showed that (1) the duration of soaking affected the adsorptionpower of the maceration result of the Ag level in the silver industrial waste in Kotagede, (2)the effective adsorbent was Sansevieria extract with a two day soaking time. It could adsorpAg waste as much as 0.6154 ppm with the value of adsorption power as much as 98.307 %.Keywords: adsorbent, Ag, AAS